Strategies and Challenges in Recruiting Pregnant Women with Elevated Body Mass Index for a Behavioral Lifestyle Intervention - Jihong Liu; Sara Wilcox; Ellen Wingard; Judith Burgis; Lara Schneider; Alicia Dahl (Mary Ann Liebert, 2020)
Purpose: Pregnant women with elevated body mass index (BMI) are difficult to recruit into lifestyle studies. This article (1) summarized strategies to recruit pregnant women into a randomized trial, and (2) reported recruitment statistics and their correlates. Materials and Methods: African American and white women with BMI ?25 and gestational age <16 weeks were recruited primarily through obstetric clinics into the Health in Pregnancy and Postpartum study. Women completed a brief screening form, and if initially eligible, a phone screening. We compared characteristics of those randomized versus not randomized. Results: Initially eligible pregnant women (N?=?1578) were identified through direct recruitment by research staff, indirect recruitment by clinic staff at obstetric clinics, and self-referrals through advertisements. Of these women, 54.0% (850) were reached for further screening, and 43.5% (685) were fully eligible. Among eligible women, 58.8% (403) were scheduled for a baseline visit, and 33.3% (228) were randomized. The overall recruitment yield was 14.4%. Recruited participants were diverse (44% African Americans) and averaged 12.6 weeks gestation at baseline. Randomized (vs. nonrandomized) women were more likely to own a cell phone, have access to a computer with internet at home or work, and have downloaded a podcast. Conclusions: Although this study did not reach the recruitment goal, a relatively large and diverse sample of pregnant women were recruited early in pregnancy. Recruiting women with elevated BMI for a behavioral lifestyle intervention is challenging, particularly among women with characteristics, including less phone and internet access and limited experience in using podcasts. This study is registered at Clinicaltrials.gov: NCT02260518.